Efeito da terapia laser de baixa potência sobre o fluxo salivar, níveis de eletrólitos, amilase, catalase e qualidade de vida em pacientes irradiados em região de cabeça e pescoço - Louzeiro, Gabriel Campos (2020)
Head and neck radiotherapy causes irreversible damage to the salivary glands, resulting in changes in flow and salivary composition. This leads to a considerable worsening of the patient's quality of life. Low-level laser therapy (LLLT) uses light energy to increase cell metabolism and its application could minimize the damage of ionizing radiation to the salivary glands. This thesis aimed to analyze the effect of LLLT concomitant with radiotherapy on salivary dysfunction in patients with head and neck cancer, through two studies: a systematic review and a randomized clinical trial. The systematic review compared the effect of LLLT with other control modalities on radioinduced hyposalivation. The randomized clinical trial evaluated the effect of LLLT compared to placebo treatment, on salivary flow, composition and pH, xerostomia symptoms and quality of life in patients undergoing head and neck radiotherapy. A systematic search was carried out in the following databases: Embase, Medline/Pubmed, Cochrane, Ebsco, Scopus, Lilacs and Web of Science. Data from studies that met the inclusion criteria were extracted and computed in a meta-analysis. The meta-analysis showed a significant increase in unstimulated salivary flow (MD 0.32 ml/min, CI 0.19-0.45, i²=94%, p<0.00001) and stimulated (MD 0.89 ml/min, CI 0.46-1.31, I²=93%, p <0.00001) with LLLT, during radiotherapy treatment. In the clinical trial, 21 patients were divided into two groups: laser group (LG) and sham group (SG). The LG received intra and extra oral laser irradiation during the entire period of radiotherapy treatment, while the SG received placebo treatment. Salivary flow, pH, composition and dry mouth analysis were performed in the following periods: before radiotherapy (T1), in the 15th radiotherapy session (T2), in the last radiotherapy session (T3) and after 2 months (T4). Quality of life analysis was performed at times T1 and T4. In contrast, the clinical trial only showed an increase in the pH of unstimulated saliva in T3 (p = 0.037) with LLLT. LLLT presents a great heterogeneity of results. The difference between studies may be related to the different protocols used. However, LLLT seems to be a valid option for the management of radioinduced salivary dysfunction.